Exploitation of national or local workers and the liability of the employer - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2013)
This chapter discusses the exploitation of national or local workers and the circumstances in which the employer would be held liable for his actions and conduct. Given the fact that the circumstances in which a worker may be subjected to exploitation are numerous, this chapter will only cover some of the selected circumstances. An employee who has been subjected to exploitation may resign from employment and thereafter file an action against the employer for an alleged constructive dismissal. The remedy for constructive dismissal is also featured in this chapter.